HUBUNGAN KEPEMIMPINAN, MOTIVASI DAN KOMPENSASI TERHADAP KEPUASAN KERJA PERAWAT RAWAT INAP RSUD SIDIKALANG KABUPATEN DAIRI TAHUN 2018 - YESSY SYAHRADESI (LP2MTBM MAKARIOZ, 2019)
Job satisfaction is influenced by many factors, one of which is Hezberg's theory of motivation factors. Empirically leadership influences job satisfaction by 66.1%. in addition compensation also has an effect on satisfaction, seen from the results of research by I Putu and Komang with a significance value of 0,000. From the survey conducted and the problems that occurred in Sidikalang Hospital regarding the lack of job satisfaction for nurses regarding the leadership of the head of the room, work motivation, and compensation. This study aims to determine the relationship of Leadership, Motivation and Compensation with Nurse Job Satisfaction in Sidikalang Hospital, Dairi District in 2018. This study used an analytical survey approach with a cross sectional design. The population was 75 inpatients inpatient care at Sidikalang Hospital, all of which were used as samples. Data collection is done by distributing questionnaires to inpatient nurses. Data analysis using Chi-Square test with a confidence level of 95% (p <0.05). The results showed that the leadership of the head of the room (p = 0.00), nurse work motivation (p = 0.001) and nurse work compensation (p = 0.022) had a relationship with nurse job satisfaction where the value of p <0.05. The most influential factor on job satisfaction is the leadership of the head of the room, where the value of Exp (B) is 44,246 times by showing nurses who feel dissatisfied with their work may be due to poor leadership compared to nurses who are satisfied. It is recommended for the head of the room to adopt a consultative leadership style and be responsive in increasing nurse job satisfaction